2002
DOI: 10.1071/sr01001
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur forms in bulk soils and alkaline soil extracts of tropical mountain ecosystems in northern Thailand

Abstract: Sulfur, besides phosphorus, is crucial for the nutrition of plants on tropical soils. Its availability is closely related to the turnover of soil organic matter. To get a better insight into transformation of soil S forms during the decomposition of organic matter, we studied inorganic and organic S pools in bulk samples and alkaline extracts of soils under different land uses representative of the tropical highlands of northern Thailand. Samples were taken from a cabbage cultivation, a Pinus reforestation, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
5
4
1
Order By: Relevance
“…Total soil S in the surface layers of the native subhumid tropical forest ecosystems of Kenya ranged from 2916 mg S/kg soil (Kakamega) to 3706 mg S/kg soil (Nandi) and was considerably higher than the values from grasslandderived soils of temperate and subtropical ecosystems. However, these results are in line with the values reported for a variety of forest-derived soils from tropical ecosystems (Stanko-Golden and Fitzgerald 1991, Solomon et al 2001, Mo¨ller et al 2002. The higher concentration of S in the subhumid tropical forest ecosystems of Kenya compared with the native temperate and subtropical grassland ecosystems could be broadly attributed to differences in climate, vegetation, and soil type.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Total soil S in the surface layers of the native subhumid tropical forest ecosystems of Kenya ranged from 2916 mg S/kg soil (Kakamega) to 3706 mg S/kg soil (Nandi) and was considerably higher than the values from grasslandderived soils of temperate and subtropical ecosystems. However, these results are in line with the values reported for a variety of forest-derived soils from tropical ecosystems (Stanko-Golden and Fitzgerald 1991, Solomon et al 2001, Mo¨ller et al 2002. The higher concentration of S in the subhumid tropical forest ecosystems of Kenya compared with the native temperate and subtropical grassland ecosystems could be broadly attributed to differences in climate, vegetation, and soil type.…”
Section: Resultssupporting
confidence: 89%
“…These results concur positively with the XANES analysis of organic S in humic fractions extracted from peat (Morra et al 1997) and forest-derived soils (Xia et al 1998, Solomon et al 2003, as well as with XANES spectra taken directly from peat (Martı´nez et al 2002) and organic layers of forest soils (Prietzel et al 2003). Our results agree also with those of Bettany et al (1980) and Mo¨ller et al (2002), who reported higher proportions of C-bonded S (70-84% of the total organic S) in the humic fractions of variety of temperate and tropical soils using conventional wet-chemical techniques. The dominance of organic S directly bonded to C in the surface layers of grassland-derived temperate and subtropical soils and forest-derived tropical soils could be attributed to the fact that this organic S fraction originates directly from plant exudates, root and leaf litterfall, animal residues, as well as microbial metabolites; which make up the bulk of soil organic matter input to the surface layers of these undisturbed ecosystems.…”
Section: Speciation Of Soil Organic S In Temperate Subtropical and supporting
confidence: 92%
See 1 more Smart Citation
“…These results concur positively with the suggestions of Lowe (1964), McLaren et al (1985), Schindler and Mitchell (1987) and Zhao et al (1996) that ester-SO 4 S can be stabilized independent of the main moiety of organic matter, may represents slightly more labile organic S fraction that can serves as a readily available S pool through biochemical mineralization process. In contrast to these findings, however, other studies using incubation and field experiments (Freney et al, 1975;McLaren and Swift, 1977;Ghani et al, 1991;Solomon et al, 2001;Mö ller et al, 2002) indicated that relatively larger proportion of SOS loss following land-use changes occurs from C-bonded S than ester-SO 4 S and stated that this organic S fraction represents the major source of mineralizable S in soils supporting the suggestion by McGill and Cole (1981). This view was also supported by our previous investigation using S XANES spectroscopy where Cbonded S (SOS in highly reduced and intermediate oxidation states) forms seems to represent the more labile forms of SOS compounds compared to ester-SO 4 S (SOS in highly oxidized states) forms and the dynamics of organic S was primarily driven by SOC turnover (Solomon et al, 2003(Solomon et al, , 2005.…”
Section: Effects Of Cultivation On Organic S Forms In Bulk Soils and contrasting
confidence: 56%
“…All extractions were made on triplicate samples. Although most S speciation studies (Neptune et al, 1975;McLaren and Swift, 1977;Lehmann et al, 2001;Mö ller et al, 2002) were conducted in the past using air dried soils, it is worth mentioning the fact that this sample preparation procedure may have some effect on the proportions of extractable organic S and sulfate S (Watkinson and Kear, 1996;Tan et al, 1994), and thus direct comparison of results should be limited to investigations using similar sample preparation strategy.…”
Section: Chemical Analysismentioning
confidence: 97%